Teaching Second Language For Young Learners: Is Earlier Always Better? - Chang, Afnesha (Fakultas Sastra Universitas Ekasakti, 2024)
These days, Indonesian children are very interested in multilingual education. Not only do they learn the second language in school, but they are also exposed to it at home. Although bilingual education has been an option for schooling for more than 50 years in many nations, there is still debate over it, particularly with regard to whether it is suitable for all students. Then, even if there are still certain misconceptions in society, some parents refuse to change because they believe bilingualism benefits their children's development on both a linguistic and cognitive level. This review looks at studies assessing how bilingual education affects students' language and literacy proficiency, academic success. Particular focus is given to variables like the environment, which influences children with bilingual education. Here, several common misconceptions about bilingualism in early life were discussed and professional scientific justifications were given. The findings demonstrate that bilingualism fosters children's concurrent robust executive functioning and improved language development.